Caracterización fincas agroecológicas del departamento del Meta, Colombia - Zárate Lozada, Juan Pablo; Valencia Vélez, Valeria; Villamizar Castro, Hernando Arturo (Pontificia Universidad Católica del Perú, 2025)
The global food system is increasingly constrained by environmental degradation and biodiversity loss, leading to drastic climate changes and exacerbating rural poverty. In response, the Sustainable Development Goals (SDGs), framed within the 2030 Agenda, aim to establish a transformative vision toward sustainability, both for and from the territories. Within this context, agroecology faces multiple challenges in promoting food security and sovereignty. Knowledge Gap: There is a significant lack of statistical and descriptive information, from both quantitative and qualitative perspectives, regarding agroecological farms in the Meta department. This underscores the necessity for future research to register such data at the regional level to provide insights into the challenges and opportunities associated with the adoption of agroecological practices. Purpose: The primary objective of this research is to characterize the farms in the department that implement agroecology as a production methodology, aiming to conduct a comprehensive analysis of the socio-environmental and economic dynamics. This will yield information for subsequent interpretation, with the goal of understanding the complexity and integrative approach of these systems. Methodology: The research employs a non-experimental, cross-sectional methodology to characterize agroecological practices and production system management in nine farms within the Meta department. These farms, located in the subregions of Ariari, the Cordillera, Altillanura, and the Capital Cordillera, were previously identified and recognized for their sustainable activities. A statistical analysis was conducted through surveys based on indicators such as productivity, diversity, water resources, as well as a deep understanding of subjective aspects like the producers' perceptions, educational level, and commercialization practices. Results and Conclusions: The studied agroecological farms exhibit diversity, with no common crop observed across the farms, in their production and management, highlighting the importance of conserving natural resources, adopting sustainable technologies, direct consumer marketing through local markets, and the combination of traditional knowledge with technical advice. These factors contribute to promoting sustainability and food security within their communities.

El sistema alimentario mundial se ve cada vez más limitado debido a la degradación ambiental y la pérdida de biodiversidad, lo que provoca cambios drásticos en el clima y aumenta la pobreza rural. En este contexto, la agroecología enfrenta múltiples desafíos en pro de la seguridad y soberanía alimentaria. Asimismo, existe una escasez notable de información en términos estadísticos y descriptivos, mediante una perspectiva cuantitativa y cualitativa, sobre las fincas agroecológicas presentes en el departamento del Meta, por lo que se hace fundamental, en futuras investigaciones, registrar dichos datos a nivel regional, con el objetivo de proporcionar información sobre los desafíos y oportunidades asociados a la adopción de prácticas agroecológicas. Por ello, el objetivo principal de esta investigación fue caracterizar las fincas productoras en el departamento del Meta, a partir de agroecosistemas que implementan la agroecología como metodología para la producción, buscando realizar un análisis exhaustivo de las dinámicas socioambientales y económicas, obteniendo información para su posterior interpretación, con el fin de comprender la complejidad de estos sistemas y su enfoque integral. La metodología aplicada en la investigación fue no experimental de manera transversal, caracterizando prácticas agroecológicas y manejo de sistemas de producción en nueve fincas del departamento del Meta, previamente identificadas y reconocidas por sus actividades sostenibles y sustentables, ubicadas en la subregión del Ariari, de la cordillera, Altillanura, y Capital cordillera. Mediante encuestas, se logró un análisis estadístico basado en indicadores de productividad, diversidad y recurso hídrico, complementado con una exploración profunda de aspectos subjetivos, como las percepciones, experiencias y conocimientos de los productores, incluyendo su nivel educativo y la forma en que comercializan sus productos. Los resultados indican que las fincas agroecológicas estudiadas muestran una amplia diversidad, es decir, no cuentan con un cultivo en común ni con la misma producción y gestión, destacando la importancia de la conservación de recursos naturales, la adopción de tecnologías sostenibles, comercialización directa al consumidor desde los mercados locales y la combinación de conocimiento tradicionales con asesoramiento técnico, logrando promover la sostenibilidad y la seguridad alimentaria en sus comunidades.
Characterization of Agroecological Practices on Farms in the Department of Meta, Colombia
Keywords: Biodiversity; Environmental conservation; Rural development; Productivity; Colombia; Biodiversidad; Conservación ambiental; Desarrollo rural; Productividad; Colombia; https://purl.org/pe-repo/ocde/ford#2.07.01